Merging of Think Pair and Share and Talking Stick Cooperative Learning Models - Nury Azkiya Umamy; Jiah Jiah; Canly Canly; Budianto Budianto; Faya Harsiyana Lestiani (Proceedings of The ICECRS, 2020)
Learning models play an important role in the success of learning in the classroom. Therefore, teachers are encouraged to always use models in every leaning. In connection with the available leaning models, we try to combine Think Pair and Share and Talking Stick models because we want to try and examine how influential these two models are when combined, and what are the impacts on teachers and students.